A Facile Air‐Retreatment Strategy for Efficient Inverted Perovskite Solar Cells. Issue 6 (31st March 2020) - Dai, Zhongjun; Xiong, Jian; Zhan, Shiping; Fan, Baojin; Zhao, Qian; Liu, Weizhi; He, Zhen; Yang, Bingchu; Yang, Junliang; Xue, Xiaogang; Zhang, Jian
Abstract : A simple air‐retreatment strategy is proposed to improve the performance of the inverted perovskite solar cells (PSCs). This air‐retreatment impact on the physical properties and corresponding performance of the devices is systematically studied. The results show that the grain size of perovskite films is enhanced by this method, and the high quality of MAPbI3 films is successfully prepared. The average grain size of 3.91 μm and the largest grain size exceeding 9 μm are achieved, and the trap states are reduced from 4.05 × 10 16  cm −3 to 1.60 × 10 16  cm −3 . Benefitted by the relatively larger grain size, lower trap density, and higher crystallinity, a high power conversion efficiency (PCE) of 18.44% and negligible hysteresis are obtained. This air‐retreatment strategy has great potential in the large‐scale, low‐temperature preparation of efficient and stable PSCs. Abstract : The largest grain size exceeding 9 μm and the high quality of MAPbI3 films are successfully prepared via a facile air‐retreatment strategy. The optimal solar cell device shows a high power conversion efficiency of 18.44% and negligible hysteresis. This strategy has great potential in the large‐scale, low‐temperature preparation of efficient and stable perovskite solar cells.